Mother tongue interference in translating engineering ESP terminology: Issues and implications - Bojaxhi, Jola; Kanini, Vanina; Shehu, Isida; Brahja, Anjeza; Stojani, Edita; Daci, Silvana (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of mother tongue interference on the translation of English for Specific Purposes (ESP) terminology by engineering students at the Polytechnic University of Tirana. The main objective is to identify the linguistic challenges students face when translating technical terms from English into Albanian and to explore effective pedagogical strategies to mitigate such interference. The research employed a mixed-methods approach, combining translation exercises, student questionnaires, and semi-structured interviews with ESP instructors. The findings reveal that the most frequent difficulties involve lexical gaps due to the lack of standardized Albanian equivalents, literal translation errors, and syntactic transfer from the mother tongue. Moreover, over 70% of students admitted to thinking in Albanian before expressing ideas in English, which often leads to structural inaccuracies. The study concludes that mother tongue interference remains a key obstacle in developing ESP competence and translation accuracy. It recommends integrating bilingual glossaries, task-based translation activities, and critical use of digital tools into ESP curricula. These implications highlight the need for a more contrastive and context-based approach to ESP teaching in Albanian higher education.